1983
DOI: 10.1111/j.1745-4549.1983.tb00661.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Maillard Browning and Other Factors on the Stability of Free Tryptophan

Abstract: The influence of various factors on the stability of free tryptophan was evaluated in several reaction systems. After treatment, tryptophan was measured by high performance liquid chromatography. Factors such as heating, protein, and glucose were responsible for tryptophan losses in a system undergoing Maillard browning. Hydrogen peroxide caused extensive losses while pH and light had minimal effect on tryptophan stability in solution. When the stability of tryptophan was compared to lysine and threonine durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Chemical transformations of tryptophan are essentially a function of the temperature and the duration of treatments. However, specific modifications can be induced by the presence of oxygen, water (Leahy and Warthesen, 1983; Kanner and Fennema, 1987), other food-oxidizing lipids (Krogull and Fennema, 1987;Nielsen et al, 1985a-d;Yong et al, 1980), vitamins (Kanner and Fennema, 1987), reducing sugars (Ashoor and Zent, 1984; Brautigam and Severin, 1974;Dworschak and Orsi, 1977;Finot et al, 1982; Nyhammar and Pernemalm, 1985;Orsi, 1985; Orsi and Dworschak, 1978;Sgarbieri et al, 1973;Tanaka et al, 1975), carbonyl compounds (Arai, 1980; Chu and Clydesdale, 1976;McLaren, 1977;Previero et al, 1972), nitrites (Bonnett and Holleyhead, 1974; Nakai et al, 1978;I to et al, 1979; Gruenwedel et al, 1984; Hotchkiss, 1984; Kinae, 1986;Mellet et al, 1986; Ochiai et al, 1986), halogens (Bercz and Bawa, 1986), radiation (Garrison, 1987), and sulfites (Yang, 1973).…”
Section: Chemistry Of Tryptophan In Foodmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical transformations of tryptophan are essentially a function of the temperature and the duration of treatments. However, specific modifications can be induced by the presence of oxygen, water (Leahy and Warthesen, 1983; Kanner and Fennema, 1987), other food-oxidizing lipids (Krogull and Fennema, 1987;Nielsen et al, 1985a-d;Yong et al, 1980), vitamins (Kanner and Fennema, 1987), reducing sugars (Ashoor and Zent, 1984; Brautigam and Severin, 1974;Dworschak and Orsi, 1977;Finot et al, 1982; Nyhammar and Pernemalm, 1985;Orsi, 1985; Orsi and Dworschak, 1978;Sgarbieri et al, 1973;Tanaka et al, 1975), carbonyl compounds (Arai, 1980; Chu and Clydesdale, 1976;McLaren, 1977;Previero et al, 1972), nitrites (Bonnett and Holleyhead, 1974; Nakai et al, 1978;I to et al, 1979; Gruenwedel et al, 1984; Hotchkiss, 1984; Kinae, 1986;Mellet et al, 1986; Ochiai et al, 1986), halogens (Bercz and Bawa, 1986), radiation (Garrison, 1987), and sulfites (Yang, 1973).…”
Section: Chemistry Of Tryptophan In Foodmentioning
confidence: 99%
“…The rate of degradation of free tryptophan during thermal treatment in a 90-140 °C temperature range is a function of pH (Leahy and Warthesen, 1983). In the presence of formate buffer, the maximum rate of decomposition occurs at pH 5.3.…”
Section: Stability Of Free Tryptophan At Temperaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the fact that tryptophan, arginine and histidine are not as abundant in milk proteins as lysine, their possible reactivity in Maillard reactions is of nutritional interest. In particular, it has been reported that tryptophan may be even less stable than lysine under some conditions (Leahy and Warthesen, 1983). Dworschak and Hegedü s (1974) reported the loss of 97% of the tryptophan in a milk powder containing 5.7% moisture that was heated at 1008C for 4 h. This conflicts with the results of Nielsen et al (1985b,c), who could not detect a decrease in tryptophan (by chemical analysis or rat bioassays) in a browned milk powder.…”
Section: Immunoassaysmentioning
confidence: 99%
“…However, Eichner and Ciner-Doruk (1979) proposed that the 1,2-E pathway assumes increasing importance as the water content increases. Significantly, a w may influence the site specificity of Maillard reactions involving proteins (Wu et al, 1990) and also the relative reactivity of individual amino acids (Leahy and Warthesen, 1983). Ideally, a w should be used as a predictor of browning rate and other spoilage reactions in foods only in the absence of moisture sorptiondesorption hysteresis (i.e.…”
Section: Moisture Content and A Wmentioning
confidence: 99%